Hyponatremia in spinal cord injury patients: new insight into differentiating between the dilution and depletion forms - Kriz, J; Schuck, O; Horackova, M (Spinal cord, 2015)
STUDY DESIGN: This is a retrospective study. OBJECTIVES: The objectives of this study were to present a new model for differentiating between the dilution and depletion forms of hyponatremia in patients in the postacute phase after spinal cord injury (SCI), and to identify possible etiological factors contributing to hyponatremia in these patients. SETTING: University Hospital Motol, Prague, Czech Republic. METHODS: Eighty-seven of 352 patients hospitalized in 2008-2012 in the Spinal Cord Unit were hyponatremic. Seventy-four patients had SNa+=130-135 mmol l(-1) and 13 patients had SNa+ below 130 mmol l(-1). We propose a simple model of an electrolyte solution in which the Na(+) concentration is higher than the Cl(-) concentration, making it possible to compare the effects of dilution and depletion of Na(+) and Cl(-) on the Na(+) concentration. The depletion of Na(+) and Cl(-) leads to a significant increase in the Na(+)/Cl(-) ratio, with the Na(+)-Cl(-) value remaining unchanged. Dilution with water results in a decrease of Na(+)-Cl(-) with the Na(+)/Cl(-) ratio remaining unchanged. RESULTS: In patients with SNa+ below 130 mmol l(-1), hyponatremia was consistent with the depletion model in 46% and with the dilution model in 32%. In patients with SNa+ ranging between 130 and 135 mmol l(-1), the respective rates were 34 and 12%. CONCLUSION: Examination of SNa+-SCl- and SNa+/SCl- in patients with SCI could be helpful in considering whether hyponatremia is consistent either with the NaCl dilution model or with the NaCl depletion model. Further studies are needed for more accurate interpretation of the results, particularly with respect to volume and acid-base disorders.
Keywords: senioři; diferenciální diagnóza; poranění míchy; Retrospective Studies; Sodium Chloride; Česká republika; Middle Aged; mužské pohlaví; Adult; Czech Republic; hyponatremie; Models, Biological; ženské pohlaví; retrospektivní studie; Humans; Hyponatremia; lidé středního věku; biologické modely; chlorid sodný; Diagnosis, Differential; elektrolyty; Electrolytes; Hospitalization; hospitalizace; dospělí; Female; Aged; Spinal Cord Injuries; lidé; Male